Efektivitas Peraturan Daerah Kabupaten Wajo Nomor 15 Tahun 2018 Tentang Penyelenggaraan Perparkiran - Andi Dadi Mashuri Makmur; Martono; MUstafa, Dewi Wahyuni; Muharawati; Fiere Lapesa Kembara (Legal Journal of Law, 2025)
This study aims to determine the Effectiveness of Wajo Regency Regional Regulation Number 15 of 2018 Concerning Parking Implementation and the efforts made by the Wajo Regency Transportation Agency. The study was conducted at the Wajo Regency Transportation Agency. In this study, the author used a qualitative analysis method. From the results of this study, to deal with parking problems, there are several efforts made by the Wajo Regency Transportation Agency, namely coaching efforts and supervision efforts. Based on the data and facts that the author has obtained, it can be concluded that the factors that influence the effectiveness of Wajo Regency Regional Regulation Number 15 of 2018 Concerning Parking Implementation are organizational effectiveness factors consisting of 1) clear objectives, 2) organizational structure, 3) community support and participation, 4) adopted value system. Second, the parking attendant work effectiveness factor which includes 1) motivation, 2) work environment, 3) parking attendant characteristics.